If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = 11x + -27 Reorder the terms: 9 + 5x = 11x + -27 Reorder the terms: 9 + 5x = -27 + 11x Solving 9 + 5x = -27 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 9 + 5x + -11x = -27 + 11x + -11x Combine like terms: 5x + -11x = -6x 9 + -6x = -27 + 11x + -11x Combine like terms: 11x + -11x = 0 9 + -6x = -27 + 0 9 + -6x = -27 Add '-9' to each side of the equation. 9 + -9 + -6x = -27 + -9 Combine like terms: 9 + -9 = 0 0 + -6x = -27 + -9 -6x = -27 + -9 Combine like terms: -27 + -9 = -36 -6x = -36 Divide each side by '-6'. x = 6 Simplifying x = 6
| (x)(4x+5)=520 | | 2y=-3x+29 | | -7x+9=19-3x | | -2y-3y+9=4-3-y | | 600=300+10c | | X^2-12x+49=22 | | 13y+2=9y+22 | | 97b=2037 | | 14x-9x=7 | | 11n^2=5n^2 | | 16b=128 | | 600=5s+400 | | x-.16x=543.90 | | 11x-4=117 | | x-.16=543.90 | | 600=175+10c | | 4n-3=4n-3 | | 4y^2+36y+72=0 | | 5/4(a-8=2/3 | | 3x[x-3]=6 | | 600=50+10c | | 7y-3y=18 | | x-0.24x=519.21 | | 2x-9+7x+13+41=180 | | y=-2(x+3)(x-4) | | x-.24x=519.21 | | 1.5y=3y | | x^3*y^3=216 | | ln(x+1)=ln(1.3) | | 5x+5-10(x+1)= | | 7-8p/2=28 | | 2x+8=4x-6 |